Photovoltaic Thermal /Solar (PVT) Collector (PVT) System Based On Fluid Absorber Design : A Review - Mohd Rosli, Mohd Afzanizam; Abdullah, Amira Lateef; Misha, Suhaimi; Tamaldin, Norreffendy; Sachit, F. A. (Penerbit Akademia Baru, 2018)

(untitled)
Photovoltaic thermal (PVT) is a hybrid system,which incorporates both thermal and electrical energy generations.PVT can be used as a cooling system for the PV system in order to enhance the electrical energy efficiency and at the same time,produce thermal energy, which can be used in other applications.There are various types of PVT collectors including water or air,based on the fluid used in the PVT system.This paper aims to review the advancement and progress in the field of PVT collector based on water fluid.The review investigated various research articles by analysing their proposed designs of PVT collector and absorber.The shortcomings and drawbacks of the available PVT collector are presented in order to show the research gap in the field of PVT collector-based water.Different PVT collectors and absorbers configurations are presented and discussed.The study concludes that water-based PVT are widely used and produce improved efficiency as compared to the air-based PVT.